2022
DOI: 10.1155/2022/1306664
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence and Deep Learning Assisted Rapid Diagnosis of COVID‐19 from Chest Radiographical Images: A Survey

Abstract: Artificial Intelligence (AI) has been applied successfully in many real-life domains for solving complex problems. With the invention of Machine Learning (ML) paradigms, it becomes convenient for researchers to predict the outcome based on past data. Nowadays, ML is acting as the biggest weapon against the COVID-19 pandemic by detecting symptomatic cases at an early stage and warning people about its futuristic effects. It is observed that COVID-19 has blown out globally so much in a short period because of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 119 publications
(177 reference statements)
0
2
0
Order By: Relevance
“…Many other works on COVID-19 diagnosis using AI-based approaches [ 83 , 84 , 85 ] were published by researchers. Chahar et al [ 86 ] and Sinwar et al [ 87 ] presented a survey of such learning models.…”
Section: Severity Identification Of Some Other Diseasesmentioning
confidence: 99%
“…Many other works on COVID-19 diagnosis using AI-based approaches [ 83 , 84 , 85 ] were published by researchers. Chahar et al [ 86 ] and Sinwar et al [ 87 ] presented a survey of such learning models.…”
Section: Severity Identification Of Some Other Diseasesmentioning
confidence: 99%
“…Over the past few years, there has been a surge in studies exploring deep learning techniques to diagnose COVID-19 and pneumonia. Systematic reviews of AI-enabled COVID-19 detection can be found in [1][2][3] in 2021, [4][5][6][7][8][9][10] in 2022, and [11][12][13] in 2023. While all reviews delved into deep learning neural networks and medical image databases, there were apparent shifts in focus, from the feasibility of deep learning to this aim and limited databases in 2021, to model performance comparison and database survey in 2022, and to model enhancement/development and real-world applications recently.…”
Section: Introductionmentioning
confidence: 99%